Contribution for the Summation Formulas for the Generalized Hypergeometric Series F65−1 - Prathima Jayarama; Dongkyu Lim; Arjun Kumar Rathie (Journal of Mathematics)
In this paper, our aim is to provide as many as one hundred and ninety-two summation formulas for the generalized hypergeometric series F65−1 in terms of gamma functions. For this, we have established eight theorems containing general results. This is achieved by means of applying generalized Watson’s and Dixon’s summation formulas obtained earlier by Lavoie et al. into a known transformation formula available in the literature. Results obtained earlier by Zhao follows special cases of our main findings.